Development of readout chain for CBM Projectile Spectator Detector at FAIR. (December 2020) - Finogeev, D; Guber, F; Karpushkin, N; Makhnev, A; Morozov, S; Serebryakov, D
Abstract: The Compressed Baryonic Matter (CBM) experiment at FAIR needs a detector to measure the nucleus-nucleus collision centrality and orientation of the reaction plane. The Projectile Spectator Detector (PSD) as a sampling lead/scintillator forward hadron calorimeter with transverse and longitudinal segmentation will be used for this purpose. The PSD consist of 44 modules with 10 longitudinal sections in each. Electronics of PSD consist of MPPCs boards mounted directly on detector and readout ADC interface with ADC FPGA board installed into crate distanced on 50m from detector part. ADC has 14-bit resolution and 125MHz digitization rate, Kintex-7 FPGA is placed on the board. Concept of PSD Front End Electronics (FEE) is already designed and most crucial parts including ADC FPGA board already tested and confirmed to be operational. One PSD module ("mini PSD" or mPSD) has been installed into the "mini CBM" (mCBM) assembled at SIS18 accelerator in GSI, Darmstadt, Germany in the framework of the FAIR Phase-0 program. ADC FPGA readout board has been integrated into common DAQ experiment and tested. Details of the mPSD FEE design and test results are shown.